State of climate smart agriculture (CSA) practices in the North Central and Northwest zones Nigeria - Isaiah Gabriel; Frank Olajuwon; Dominik Klauser; Blessing Michael; Mara Renn (CABI Agriculture and Bioscience)
Abstract Agriculture is exposed to climate change. This is particularly the case for developing countries like Nigeria, which suffer from persistent food insecurity today while also facing substantial population growth and a high exposure to the adverse consequences of global warming. Climate-smart agriculture (CSA) practices seek to mitigate agriculture’s contribution to climate change while building resilience and adaptation to the impacts of climate change and increasing the production of food crops. CSA is an approach to identify production systems that can best respond to the impacts of climate change and to adjust these systems to suit local conditions. In this study, we use descriptive statistics to characterize socio-economic characteristics of smallholder farmers in four states in Nigeria and identify the major needs, practices and constrains to CSA. Our results reveal that the mean farmer is an adult (40 years) male that has 10 members in their household and 12 years of farming experience, cultivating an area of 3 ha. The majority (87.2%) of farmers has adopted at least one climate resilient trait in crops. Farmers greatest needs on climate smart adaptation, mitigation and profitability were solutions to reduce in-season crop loss (56%), increase water use efficiency (42%) and increase productivity (54%), respectively. Our study intends to provide to a better understanding of the needs and motivations of local farming communities and a better understanding of their motivation to engage in CSA to develop and deploy more tailored initiatives for improving the resilience and productivity of smallholder farming systems.